Analysis of the Role of Indonesia's Active Free Diplomacy in Resolving the Rohingya Conflict - Rahmat Kartiwa; Zakiah Jalianty (Social Impact Journal, 2023)
The conflict between the Myanmar government led by a military junta and the Rohingya Muslim tribe is one of the most tragic and heartbreaking human tragedies. The suffering experienced by the Rohingya tribe certainly hurts security in the Southeast Asia region. This research aims to find out how Indonesian diplomacy based on the principle of free and active foreign policy can resolve the Rohingya conflict in Myanmar. The humanitarian conflict affecting the Rohingya ethnic group in Myanmar has raised deep concern among the international community, including Indonesia. Diplomacy is an important instrument in implementing a country's foreign policy. Successful diplomacy can add value to a country and improve its image in the eyes of the world. This research uses a qualitative approach with a literature study method. The data sources for this research are books and journals related to analyzing the role of Indonesia's free and active diplomacy in resolving the Rohingya conflict. The results of this research indicate that to increase the success of Indonesian diplomacy in resolving the Rohingya conflict, more intensive and comprehensive efforts are needed. Indonesia needs to work together with other countries at various levels to encourage the Myanmar government to resolve the conflict peacefully and fairly by human rights principles.